STRATEGI KOMUNIKASI KPU KABUPATEN BANYUMAS DALAM SOSIALISASI PILKADA 2018 DAN PEMILU 2019 KEPADA KELOMPOK DISABILITAS - alfian muhazir; Feby Irawan; Alfiyyah Nur Fadhilah (Jurnal Ilmu Komunikasi PROGRESSIO, 2022)
Election socialization is an important and strategic phase in the holding of elections. Socialization is needed as a means of organizing elections in facilitating the needs of voters in the election period. KPU as the organizer of the General Election has the responsibility of providing socialization to the public. KPU of Banyumas Regency has established a program of Volunteer of Democracy (Relasi) as a partner of KPU in carrying out socialization in order to increase voter participation and voter quality in using voting right. This research about how Communication Strategy of KPU’s Banyumas Regency in socialization Election 2018 and Election 2019 to Disability Groups in Garut Regency. This research method using qualitative approach by using observation technique and interview for data collection in order to get objective data. The theory used is the Communication Strategy initiated by Dan O'hair (2009) who uses three main areas, namely; situational knowledge, goal setting, and communication competence. The result of this research is that communication strategy conducted by Election Commission (KPU) of Banyumas Regency in the dissemination of elections in 2018 and elections in 2019 to Disability Groups is effective because it can utilize the potential in three main areas, namely: Situational Knowledge, Determination of Goals and Communication Competencies. However, there are some notes of the evaluation of socialitation program of disability group, such as; the pattern of the KPU’s Banyumas Regency approach in the future is expected to be more specific in accordance with the level of disability of each disability group, the need for involving the community of SLB’s teachers as the assistance of disability groups, the need for clear supporting instruments in the next election socialization program, and the need for adequate funding support for socialization election against disability group can run maximally.